Potential Antimalarial Compounds from Spectroscopically Identified Compounds of Aqueous Stem-bark Extract of Magnifera indica: An In silico Approach - Abdulhafiz Lamiya; Saihana Muhammad; Adamu Jibril Alhassan; Maryam AbdulKadir Dangambo; Hauwa Ahmed Zailani (Nepal Journal of Biotechnology)
Ethnobotanical studies and phytochemical screening are invaluable approaches in the search for novel drug substances needed to confront the growing challenges faced by drugs used in the treatment of many infectious diseases malaria inclusive. This study employed spectroscopic techniques to identify major phytochemicals present in aqueous extract of Magnifera indica stem bark and in silico technique to screen the identified phytochemicals for the identification of potential Plasmodium falciparum protein inhibitors. Spectroscopic assay of the extract revealed the presence of fifteen major compounds. Molecular docking analysis of the identified compounds against some Plasmodium falciparum targets revealed that oleic acid was the top hit compound for plasmepsin II with binding energy of -5.8Kcal/mol., 9,12-Octadecadienoic acid [Z,Z]  was the top hit for histo-aspartic protease with binding energy of -6.1Kcal/mol., and Phthalic acid dibutyl ester was the to hit compound for both falcipain-2 and P. falciparum enoyl acyl carrier protein reductase with binding energy of  -5.6 and -4.9Kcal/mol respectively. ADMET analysis of these top hit compounds revealed favorable pharmacokinetics and toxicity. All the compounds poses drug like properties, high GI absorption, non-substrate to permeability-glycoprotein and safe for the major vital organs except Phthalic acid dibutyl ester which shows slight activity in nephrotoxicity. Thus, there is need for further experimental validation and optimization of the top hit compounds to improve both efficacy and toxicity.